2018
DOI: 10.21276/aimdr.2018.4.2.de13
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Smile and Esthetic among Dental and Non- Dental Student

Abstract: Background: To assess the self perception of one's own smile and its influence on their behavior and also their ability to rate different types of smiles from most attractive to least attractive on a visual analogue scale by dental and non dental students. Methods: This study was carried out by using structured questionnaire and booklet of visual analogue scale distributed to 276 students in Taif University that included Dental, Medical and Pharmacy students. Results: Medical (66%), Pharmacy (60%) and dental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…This is inconsistent with the findings of other authors who found both dental students and laypeople to be less tolerant to darker tooth shades. 12,24 As reflected in the ratings, we also found that, medical students were able to discriminate between diminutive laterals (figure 1.4) (mean = 33; SD = 24) and normally shaped laterals incisors (figure 1.1) (mean = 62; SD = 19); however, this contradicted the findings of Witt and colleagues; who found that laypeople are unable to differentiate between various shapes, forms, and sizes of maxillary incisors. 27 Furthermore, dental students tended to evaluate dental midline shifts slightly less favorably than medical students.…”
Section: Discussioncontrasting
confidence: 69%
“…This is inconsistent with the findings of other authors who found both dental students and laypeople to be less tolerant to darker tooth shades. 12,24 As reflected in the ratings, we also found that, medical students were able to discriminate between diminutive laterals (figure 1.4) (mean = 33; SD = 24) and normally shaped laterals incisors (figure 1.1) (mean = 62; SD = 19); however, this contradicted the findings of Witt and colleagues; who found that laypeople are unable to differentiate between various shapes, forms, and sizes of maxillary incisors. 27 Furthermore, dental students tended to evaluate dental midline shifts slightly less favorably than medical students.…”
Section: Discussioncontrasting
confidence: 69%
“…6% of medical and 7% of dental students used to cover their smiles with their hands. In addition, 75% of the medical students believe that someone else had a better smile than theirs, compared to 63% of the dental students [25].…”
Section: Discussionmentioning
confidence: 96%
“…The most common cause of dissatisfaction among medical interns was their tooth color, similar to the results of Alharthy and co-authors' study. They found that 76% of the medical interns wished to have whiter teeth [25]. The scientific background of the dental interns also could have an effect on spotting the complications that resulted after smile-enhancing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Dentists and laypersons have diferent esthetic perceptions [5,13,18]. In addition, dental and smile esthetic perceptions difer between dental and nondental students [19,20]. Terefore, four rater groups, including dentists, laypersons, dental students, and other faculty students, were selected for this study.…”
Section: Discussionmentioning
confidence: 99%